Academic Hardiness Scale of College Students : Validity and Reliability Analysis Using Rasch Model - Muhammad, Fadhil; Rakhmat, Cece; Rusmana, Nandang; Saripah, Ipah; Meliala, Aditia Kharisma (Universitas Pendidikan Mandalika, 2025)
This study aims to analyze the validity and reliability of the academic hardiness scale that has been developed in the context of Indonesian culture. This research method used a survey with a quantitative approach to 50 students at the University of West Sulawesi. The data analysis technique was carried out using the Rasch Model. The results of the study showed that this academic hardiness scale was quite good at describing the profile of students' academic hardiness with a raw variance explained value of 38.8%. This scale was also reliable, with a person reliability value of 0.94 and an item reliability of 0.95, which reflects the consistency of the measurement. These findings have significant implications for further research in developing a guidance and counseling service program model that is more responsive to the needs of students in higher education, which is based on empirical evidence. This can be achieved by producing a consistent measurement scale to provide accurate information regarding the profile of students' academic hardiness in higher education.